Stereotactic body radiation vs. intensity-modulated radiation for unresectable pancreatic cancer. (2nd December 2017) - Park, Joseph J.; Hajj, Carla; Reyngold, Marsha; Shi, Weiji; Zhang, Zhigang; Cuaron, John J.; Crane, Christopher H.; O'Reilly, Eileen M.; Lowery, Maeve A.; Yu, Kenneth H.; Goodman, Karyn A.; Wu, Abraham J.
Abstract: Background: Stereotactic body radiation therapy (SBRT) is an emerging treatment option for unresectable pancreatic cancer, and is postulated to be more effective and less toxic than conventionally fractionated intensity modulated radiation therapy (IMRT). Material and methods: We retrospectively reviewed unresectable stage I–III pancreatic adenocarcinoma treated from 2008 to 2016 at our institution with SBRT (five fractions, 30–33 Gy) or IMRT (25–28 fractions, 45–56 Gy with concurrent chemotherapy). Groups were compared with respect to overall survival (OS), local and distant failure, and toxicity. Log-rank test and Cox proportional hazards regression model, and competing risks methods were used for univariate and multivariate analysis. Results: SBRT patients ( n  = 44) were older than IMRT ( n  = 226) patients; otherwise there was no significant difference in baseline characteristics. There was no significant difference in OS or local or distant failure. There was no significant difference in rates of subsequent resection (IMRT =17%, SBRT =7%, p  = .11). IMRT was associated with more acute grade 2+ gastrointestinal toxicity, grade 2+ fatigue, and grade 3+ hematologic toxicity ( p  = .008, p  < .0001, p  = .001, respectively). Conclusions: In this analysis, SBRT achieves similar disease control outcomes as IMRT, with less acute toxicity. This suggests SBRT is an attractive technique for pancreatic radiotherapy because of improved convenience and tolerability with equivalent efficacy. However, the lack of observed advantages in disease control with this moderate-dose SBRT regimen may suggest a role for increasing SBRT dose, if this can be accomplished without significant increase in toxicity.